Efektifitas Metode Proyek dalam Meningkatkan Keterampilan Vokasional membuat Lampu Hias dari Sendok Plastik bagi anak Tunarungu - Awaliyah, Iqlimatul; Efendi, Jon (Jurnal Penelitian Pendidikan Khusus, 2022)
This study discusses the problems at SLB N 2 Pariaman where vocational learning has been taught in schools, but this vocational learning has stopped because there are no new skills that will be given to children. Therefore, the teacher asks for new skills and learning methods that will increase children's interest in learning. Therefore, researchers want to teach a vocational skill to make decorative lights from plastic spoons to deaf children. This study aims to determine whether the project method is effective in improving skills in making decorative lamps from plastic spoons in deaf children at SLB N 2 Pariaman. The research method used by the researcher is using the pre-experimental design pretest and posttest methods. Where later the results of the pretest and posttest that have been sought are compared by testing the research hypothesis. Then it can be tested using the WilcoxonSign Rank Test analysis test. From these results, the probability value or Asymp.sig (2-tailed) is 0.042. The results of this study indicate that the Asymp.sig (2-tailed) value of 0.042 is small compared to the predetermined significance level of 0.05 (0.042 < 0.05). Therefore, it can be concluded that the project method is effective in improving vocational skills in making decorative lamps from plastic spoons for deaf children at SLB N 2 Pariaman.